Management of surgical procedures in children with severe FV deficiency: experience of 13 surgeries. (23rd November 2012) - Mathias, M.; Tunstall, O.; Khair, K.; Liesner, R.
Summary Homozygous severe factor V (FV) deficiency has a prevalence of around one per million. Even in patients with FV levels of <0.01 IU mL−1 there appears to be a variation in bleeding phenotype in that there is a subgroup of affected individuals who present in later childhood and have a relatively mild bleeding phenotype, but there are children who present as neonates with intracerebral bleeding events and who have a much more severe bleeding phenotype. The only available current FV replacement is in the form of fresh frozen plasma (FFP) or solvent detergent FFP. We present here our experience with surgical haemostatic cover for 13 surgeries in three children with severe FV deficiency.